Funciones de los trabajadores de la empresa FUTURCORP S.A - Mora Muñoz, Dayana Elizabeth (2018)
The present case study is developed based on the need to determine actions that allow the company FUTURCORP S.A del cantón Puebloviejo, improve the level of satisfaction in relation to work functions that the workers carry out in the process of making the banana puree; using this product as a sales strategy to capture a larger segment in the national and international market.